2017
DOI: 10.3389/fnut.2017.00063
|View full text |Cite|
|
Sign up to set email alerts
|

Taheebo Polyphenols Attenuate Free Fatty Acid-Induced Inflammation in Murine and Human Macrophage Cell Lines As Inhibitor of Cyclooxygenase-2

Abstract: Aim of studyTaheebo polyphenols (TP) are water extracts of Tabebuia spp. (Bignoniaceae), taken from the inner bark of the Tabebuia avellanedae tree, used extensively as folk medicine in Central and South America. Some anti-inflammatory drugs act by inhibiting both cyclooxygenase-2 (COX-2) and COX-1 enzymes. COX-2 syntheses prostaglandin (PG) E2, which is a species of endogenous pain-producing substance, whereas COX-1 acts as a house-keeping enzyme. Inhibiting both COX-1 and -2 simultaneously can have side effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The main finding of the present study is that TP administration enhanced endurance capacity via up-regulation of muscle glycogen levels. Several studies which investigated the effects of taheebo extract have reported that taheebo has anti-cancer, anti-obesity, anti-inflammation and antioxidant effects 20 – 23 , 26 . The present study is the first report that lights up the mechanisms by which TP benefits endurance capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The main finding of the present study is that TP administration enhanced endurance capacity via up-regulation of muscle glycogen levels. Several studies which investigated the effects of taheebo extract have reported that taheebo has anti-cancer, anti-obesity, anti-inflammation and antioxidant effects 20 – 23 , 26 . The present study is the first report that lights up the mechanisms by which TP benefits endurance capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Mattos; ], a medicinal plant with extensively use as folk medicine in Central and South America, as an anti-inflammation agent without undesirable side effects from COX-1 inhibition. This work was conducted using in vitro free fatty acid-stimulated macrophage cell lines and combined molecular docking to investigate the interactions between the phenolic compounds and COX-2; the obtained results illustrated anti-inflammatory effects of phenolics from this medicinal plant to regulate macrophages by targeting COX-2 activity inhibition without any action on COX-1 activity [ 71 ]. Furthermore, phenolics and flavonoids from bark of Vitex peduncularis Wall.…”
Section: Effects Of Plant Flavonoids and Other Phenolics On Human mentioning
confidence: 99%
“…The concreted example can be seen in the study of Kaczmarczyk-Sedlak and his research group; their results indicated that moderate dose of isoflavane glabridin from root of Glycyrrhiza glabra L. or licorice plant showed no effect on bone loss in ovariectomized rats, an in vivo model of osteoporosis from estrogen deficiency in postmenopausal women [ 103 ]. The secondary metabolites discovered in medicinal plants such as flavonoids and other phenolics may avoid the negative side effect of synthetic medicines, because they must accumulate within the cells and tissues of living organisms [ 71 , 95 , 96 ]. Moreover, many medicinal herbs contain novel or valuable secondary metabolites with different biological properties, and a huge numbers of them are waiting for discovery.…”
Section: Naturally Occurring Plant Phenolics and Flavonoids For Mementioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal permeability increases following exercise, and endotoxemia occurs, which induces systemic inflammation [ 4 , 39 , 43 , 44 ]. Therefore, other countermeasures such as intake of some functional foods for gut barrier protection, bioavailability, and distribution [ 3 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], and appropriate immune responsiveness should be examined in future studies.…”
Section: Examples Of Countermeasures To Exercise-induced Inflammatmentioning
confidence: 99%